Assessing performance of the Healthcare Access and Quality Index, overall and by select age groups, for 204 countries and territories, 1990-2019: a systematic analysis from the Global Burden of Disease Study 2019 - Haakenstad, Annie; Bärnighausen, Till; Brenner, Hermann; Chen, Simiao; Jonas, Jost B.; Moazen, Babak (The lancet. Global health, 2022)
Health-care needs change throughout the life course. It is thus crucial to assess whether health systems provide access to quality health care for all ages. Drawing from the Global Burden of Diseases, Injuries, and Risk Factors Study 2019 (GBD 2019), we measured the Healthcare Access and Quality (HAQ) Index overall and for select age groups in 204 locations from 1990 to 2019.
GBD 2019 Healthcare Access and Quality Collaborators: Annie Haakenstad, Jamal Akeem Yearwood, Nancy Fullman, Corinne Bintz, Kelly Bienhoff, Marcia R Weaver, Vishnu Nandakumar, Jonah N Joffe, Kate E LeGrand, Megan Knight, Till Winfried Bärnighausen, Hermann Brenner, Simiao Chen, Jost B Jonas, Babak Moazen [und 413 weitere]
Gesehen am 19.01.2023
Dateiversion vom 16. November 2022